Monitoring Hypertension Group Regularly and Intensively with Officers and Cadres (Fit Heart Group) as an Effort to Increase the Knowledge of Elderly Cadres about Controlled Hypertension: Pemantauan Kelompok Hipertensi Secara Rutin dan Intensif Bersama Petugas dan Kader (Kelompok Jantung Sehat) sebagai Upaya Meningkatkan Pengetahuan Kader Lansia tentang Hipertensi Terkendali - Maria, Kiki; Siswanto, Heri; Rahman, Zaiful; Rondhianto; Kudlori, Ahmad (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Controlled hypertension is a health problem that is closely related to mortality. The prevalence of this disease increases significantly every year throughout the world. Failure in self-awareness results in decreased self-control and decreased self-efficacy, resulting in patients not having regular control and not regularly taking hypertension medication. This study aims to increase the knowledge of female cadres about controlled hypertension. Using pre-test and post-test results of elderly cadres in blood pressure measurement training for hypertensive patients with the T-Test. Inclusion criteria of elderly cadres who have a blood pressure measurement training certificate at the UPTD Tegalampel Public Health Center. The 20 elderly cadres who took part in blood pressure measurement training with using T-Test to see the effect of training for elderly cadres toward blood pressure measurement level of knowledge. Based on the results of the T-Test, there was no significant improvement after health education regarding the prevention and treatment of hypertension (p=0.115). Given to the level of knowledge of elderly cadres regarding blood pressure measurement training. This is caused by increased self-awareness, self-control, and self-efficacy. Efforts to increase the level of knowledge of elderly cadres about controlled hypertension can increase self-awareness by forming a healthy heart group (the hypertension group is supervised regularly and intensively by officers and cadres) by forming a WA group, training elderly cadres with blood pressure measurement training and therapy counseling traditional (guava leaves, garlic, cat's whiskers leaves, ginger, bay leaves, noni, soursop leaves, soak feet in warm water)to increase awareness of controlled hypertension patients in improving healthy lifestyles, namely regular health checks, taking medication regularly.